A comprehensive list of the Bunyavirales replication promoters reveals a unique promoter structure in Nairoviridae differing from other virus families - Neriya, Yutaro; Kojima, Shohei; Sakiyama, Arata; Kishimoto, Mai; Iketani, Takao; Watanabe, Tadashi; Abe, Yuichi; Shimoda, Hiroshi; Nakagawa, Keisuke; Koma, Takaaki; Matsumoto, Yusuke (Scientific reports, 2022)
Members of the order Bunyavirales infect a wide variety of host species, including plants, animals and humans, and pose a threat to public health. Major families in this order have tri-segmented negative-sense RNA genomes, the 5′ and 3′ ends of which form complementary strands that serve as a replication promoter. Elucidation of the mechanisms by which viral polymerases recognize the promoter to initiate RNA synthesis is important for understanding viral replication and pathogenesis, and developing antivirals. A list of replication promoter configuration patterns may provide details on the differences in the replication mechanisms among bunyaviruses. By using public sequence data of all known bunyavirus species, we constructed a comprehensive list of the replication promoters comprising 40 nucleotides in both the 5′ and 3′ ends of the genome that form a specific complementary strand. Among tri-segmented bunyaviruses, members of the family Nairoviridae , including the highly pathogenic Crimean-Congo hemorrhagic fever virus, have evolved a GC-rich promoter structure differing from that of other families. The unique promoter structure might be related to the large genome size of the family Nairoviridae among bunyaviruses, and the large genome architecture might confer pathogenic advantages. The promoter list provided in this report is useful for predicting the virus family-specific replication mechanisms of bunyaviruses.